Étude comparée entre les adjectifs kurdes(Sorani) et français - Kareem Abdlurahman Othman (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
This study attempts to delve into the semantic differences of adjectives between Kurdish and French languages which espouse some important resources concerning this subject. French language is rather a novel area to research about among Kurdistan universities and to Kurdish students French is somehow unfamiliar to them and due to that Kurdish students face a lot of difficulties in adjectives. One of the problems Kurdish students encounter is adjectives in form and meaning, this makes Kurdish students exert more effort in that respect. This study consists of three sections. The first one deals with adjectives in French languages and giving examples for each one. The second one deals with Kurdish adjectives using some important resources in the language. The third one deals with the differences between the two languages so as to be clear for the readers to figure out their differences clearly.